Speech of words and Learning Dhamma Questions (Kradudhamma) - Susakaro, Phrakrupalad Prapan (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Speech of words is very important and necessary for learning of writing essay on dhamma questions (Kradudhamma) which is one of subjects in the Curriculum of Dhamma Studies in every level. Learning and teaching dhamma only has to have good memory, understanding and ability to apply dhamma for life, also style of writing which is the writing skill of communication for sending message through by art of choosing words. The writer should have ability of words usage tactically, clearly, beautifully and suitably for the story in propagation of Buddhist Dhamma. Speech contains five types, namely exposition, description, argumentation, narration and simile. Learning of writing essay on dhamma questions (Kradudhamma) in the 1st class of dhamma studies which is formulated by Royal Dhamma Division can evaluate the knowledge and dhamma understanding of dhamma-learners.